2005
DOI: 10.1080/014850190924115
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Modulation of Proliferation of Thymocyte by Testosterone, Dehydroisoandrosterone and Androstenedione in Vitro

Abstract: & Although the relationship between androgens and the immune system has been well established, the immunomodulatory function of different kinds of androgens on the cellular immunity remains to be defined. In the present study, the in vitro influences of testosterone, dehydroisoandrosterone and androstenedione on the Con A induced proliferation of thymocyte were determined. The results showed that both dehydroisoandrosterone and testosterone suppressed the Con A induced proliferation of thymocyte, while dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…However, Yao et al. [38] have demonstrated recently that the androgen structure is determinant in resulting in either the inhibition or the enhancement of LT proliferation. Thus, the authors have demonstrated that small structural changes of androgens (testosterone, DHEA or androstenedione) can result in markedly different biological effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Yao et al. [38] have demonstrated recently that the androgen structure is determinant in resulting in either the inhibition or the enhancement of LT proliferation. Thus, the authors have demonstrated that small structural changes of androgens (testosterone, DHEA or androstenedione) can result in markedly different biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been carried out in order to elucidate the DHEA effects on the activation and proliferation of lymphocytes, but have resulted in controversial results [19,37]. However, Yao et al [38] have demonstrated recently that the androgen structure is determinant in resulting in either the inhibition or the enhancement of LT proliferation. Thus, the authors have demonstrated that small structural changes of androgens (testosterone, DHEA or androstenedione) can result in markedly different biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Conversion is usually more pronounced in young women and women with selected FMR1 genotypes/ subgenotypes (69). DHEA and testosterone also suppressed canavalin A (Con A)-induced proliferation of thymocytes in vitro, and DHEA is less potent than testosterone, which means that the balance between the two steroids can alter immune homeostasis (70). Testosterone and estradiol levels vary widely after DHEA administration, and the testosterone to estradiol ratio increased significantly in seven healthy nonobese postmenopausal women (71).…”
Section: Conversion To Other Steroidsmentioning
confidence: 99%
“…Glucocorticoids, like the sex steroids, contribute to thymic involution (55), and DHEA has also been reported to have an apoptotic effect in thymic cells (68), while its metabolites androstenedione and DHEA-S have been reported to have opposite effects, with DHEA-S being antiapoptotic (70) and androstenedione stimulating thymocyte growth (69). The effect of thyroid hormone is biphasic with low doses being stimulatory (55), while too high doses may cause thymic atrophy (55).…”
Section: Introductionmentioning
confidence: 98%